(untitled) - Brigham, Eugene F. (Fort Worth, 1998)
The market leader, Brigham/Houston continues to grow in reputation as the most effective approach for student learning in the first undergraduate corporate finance course. It is also updated to reflect the latest in theory, research, real-world examples, and the use of technology. The seamless, integrated ancillary package - done by the authors - is a hallmark of this package that makes course preparation easier for instructors and the subject more accessible for students.
Keywords: Corporations,Tổng công ty; Finance,Tài chính